Adaptability to Clouds of Change: Study of Engineering Students Pursuing Technical Education in Online Mode - Vikrant Dhenge; Maithili Paikane; Harsh Deshpande (IAFOR Journal of Education)
The pandemic has affected the social, economic, political, and psychological as well as physiological well-being of an individual. Due to technological advancements, it was comparatively easy to adapt to these clouds of change, and the education field was not an exception. The researchers have observed this not only in letter but in spirit during the pandemic through the new way of teaching and learning, that is, the Online Learning Mode. This paper aims to study the impact of place of residence on English language acquisition and the social and psychological health of engineering students in Online learning mode. A structured questionnaire was designed for this study. A total of 245 participants who are presently pursuing engineering in online learning mode participated in the research. The study revealed that the place of residence had no influence on English language acquisition but significantly impacted engineering students’ social and psychological health.